RANCANG BANGUN APLIKASI PORTAL KOMUNITAS GEREJA KATOLIK SANTO PAULUS BERBASIS WEB MENGGUNAKAN METODE CROWDSOURCING - Kristoforus Kevin Kasomtijo; Valentinus Roby Hananto; I Gusti Ngurah Alit Widana Putra (Jurnal Sistem Informasi Universitas Dinamika, 2018)
The Catholic Church is a Catholic worship association or community. The Church of Santo Paulus, Juanda has 10 categorical groups each of which has the characteristics of different members and various activities consisting mainly of daily mass activities, holiday celebrations, joint prayer events, pilgrimages, recollections etc. which will be published through the media of the church website the. However, the website that has been owned by Santo Paulus, Juanda Church is currently less informative because of the lack of time that members of the church's social group have to update the website's news content.Based on the above problems, the Santo Paulus, Juanda Catholic church needs a web-based portal application with a crowdsourcing method that is able to integrate information of church activities into a single entity with web-based media. Using the Crowdsourcing method, the job function of updating the website's news content is redirected to openly and freely for people connected to a computer network via the Internet, so that people can be actively involved in sharing information about church activities that will or have been done.From the results of experiments conducted on web-based portal application with crowdsourcing method can be concluded that the application is able to provide complete information activities, so as to facilitate the people in knowing all the information of church activities through this web application.